To dwell within: Bridging the theory–practice gap - Zieber, Mark (Nursing philosophy, 2020)
Nursing has a considerable history of theory development but has consistently struggled to reconcile theoretical reality and practice realities. Many authors have attempted to reconcile what has been called the "theory-practice gap," but the space where these two realities enmesh has remained problematic and contentious (Aimei, Macau Journal of Nursing, 14, 2015, 13; Factor, Matienzo, & de Guzman, Nurse Education Today, 57, 2017, 82). The idea of the theory-practice gap has a significant history in nursing, but also continues to have a significant presence within nursing literature and mythology up to the present (Aimei, Macau Journal of Nursing, 14, 2015, 13). In this paper, the space between theoretic reality and practice reality, as evidenced by the theory-practice gap, will be examined. A Heideggerian perspective of "dwelling" (Heidegger, 1971, Poetry, language, thought, New York, NY: Harper Colophon) will be used as a guiding discourse to move nursing away from this classic tension between theory and practice, towards a perspective where theory and practice are woven together as part of one reality.